An insight into the effects of transition metals on the thermal expansion of complex perovskite compounds: an experimental and density functional theory investigation. Issue 26 (20th June 2018) - Wang, Xiao; Han, Ye; Song, Xiaojie; Liu, Weihui; Jin, Yinxi; Liu, Wentao; Cui, Hongzhi
Abstract : The doping of transition-metals can suppress the growth of the perovskite grain and decrease the TECs of the compounds. The mechanisms were studied using experimental methods and theoretical calculations. Abstract : ABO3 perovskite-type LaCoO3, LaCo0.5 Fe0.5 O3, LaCo0.5 Ni0.5 O3, and LaCo0.5 Mn0.5 O3 complex oxides were synthesized using the sol–gel method. The microstructure and the thermal expansion behavior of the oxides were investigated. Insights into phonon dispersion and the effects of doped transition metals on thermal expansion were obtained by first-principles calculations based on density functional theory. Thermal expansion coefficients (TECs) at finite temperatures were obtained by quasi harmonic approximation. B-site doping was found to reduce the size of the crystalline grains and the TECs of perovskite compounds. The average TECs of LaCoO3, LaCo0.5 Fe0.5 O3, LaCo0.5 Ni0.5 O3, and LaCo0.5 Mn0.5 O3 were 25 × 10 −6 K −1, 11 × 10 −6 K −1, 12.5 × 10 −6 K −1, and 5 × 10 −6 K −1, respectively, in the 0–1000 K temperature range. In addition, the TECs of LaCo0.5 Fe0.5 O3 and LaCo0.5 Ni0.5 O3 matched well with those of some common electrolytes.